Evaluasi Literasi Keuangan Syariah dan Pengaruhnya Terhadap Minat Penggunaan Layanan E-Banking Syariah - Anom Garbo; Muhamad Nur Ichsan (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
This study aims to measure the influence of the level of sharia digital financial literacy on the interest in using sharia e-banking services among MSME actors in Manisrenggo District, Klaten Regency, Central Java. A quantitative method is used in this research to determine the extent to which the level of sharia digital financial literacy affects the interest in using sharia e-banking. The level of sharia digital financial literacy is measured based on individuals' understanding of sharia financial management and their knowledge of sharia financial products and services available in digital technology. This study also considers control variables such as perceived ease of use and perceived usefulness to strengthen the estimation of interest in using sharia e-banking services. The research population includes 148 MSMEs registered in Manisrenggo District, with samples taken using purposive sampling techniques. Multiple regression analysis shows that the level of sharia digital financial literacy has a positive and significant effect on the interest in using sharia e-banking. Control variables such as perceived ease and usefulness also significantly influence this interest. The F-test also shows significant results with an F calculated value of 77.280 and an F table value of 2.766, as well as a significance value of 0.000 (<0.05), indicating that sharia digital financial literacy, perceived ease, and perceived usefulness simultaneously affect the interest in using sharia e-banking.